If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = 11x + -65 Reorder the terms: -3 + 3x = 11x + -65 Reorder the terms: -3 + 3x = -65 + 11x Solving -3 + 3x = -65 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -3 + 3x + -11x = -65 + 11x + -11x Combine like terms: 3x + -11x = -8x -3 + -8x = -65 + 11x + -11x Combine like terms: 11x + -11x = 0 -3 + -8x = -65 + 0 -3 + -8x = -65 Add '3' to each side of the equation. -3 + 3 + -8x = -65 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = -65 + 3 -8x = -65 + 3 Combine like terms: -65 + 3 = -62 -8x = -62 Divide each side by '-8'. x = 7.75 Simplifying x = 7.75
| 32/4+(3*7)*18+5 | | 10*3.14= | | 4x+6=-42-8 | | x^2+1=4x+4 | | -3x-2y=-19 | | 40+25=65+70 | | 7(4y+x)=4 | | (x-1/2)^2=41/4 | | 2(2+5p)= | | 10xn=9 | | 6x+20=92 | | 0,15(2x+4)=2(1,3+0,3)-0,6 | | 10(5+x)=7 | | 1+(5+x)= | | 10-2(x+3)=5(2x-4) | | (9y/2y+1)=9 | | 3w+15=45 | | -16.7*3+55= | | (-14.3)*6.7*(-5.8)=x*(-5.8)*(-14.3) | | -43-(-29)=x/2 | | -12b+(-3b)+19b-(-11)=3 | | 12+x=-3+4x | | k*6481792357659=795315987*479815479 | | 18g-8g=10 | | 20u+(-14u)-20u=14 | | math+3=654545 | | ab+2b-6-3a= | | 0,7(x+2)=0,4(x+1)+0,3x+1 | | 7+j=4435435434 | | 7d-6d+4d-2d=9 | | 7+o=555546426442445 | | 6j-3j+2j+5j=20 |